THE INFLUENCE OF CURRENT AND VOLTAGE HHO GENERATOR SETTINGS AGAINST GENERATOR ACHIEVEMENT - LEO AGUSTA (NIM : 13105057); Pembimbing 1 : Dr. Ing. Tri Yuswidjajanto Zaenuri; Pembimbing, MUHARRAM
Energy crisis certainly occur if fossil fuel consumption is not suppressed early on, one of the many ways to save fossil fuel is to use an additional tool that makes combustion more efficient or increase the combustion energy. Nowadays widespread use of these oksyhydrogen is happen and the makers claim that this tool increase engine efficiency. My Final task is to test the effect of additional oxyhydrogen into four stroke gasoline engine that drives the electric generator by entering the oxyhydrogen gas directly at the modificated intake, voltage and current supply optimization to the HHO generator needed to get the relationship between a given amount of energy into the oxyhydrogen gas producer with achievement fuel consumption of generator set engine. The results of this test states that there have been savings, increase of thermal efficiency, SFC decreased, increased Torque and Power The use of oksyhydrogen gas indeed have an effect into the combustion, but one thing that must be considered is the optimal ratio between the amount of oxyhydrogen gas with load and make sure the water that used for electrolysis not go into combustion chamber